2024
DOI: 10.1038/s44159-024-00280-6
|View full text |Cite
|
Sign up to set email alerts
|

A social ecological approach to belonging in LGBTQ+ people

Jes L. Matsick,
Jude T. Sullivan,
Emerson Todd
et al.

Abstract: People who identify as lesbian, gay, bisexual, transgender, and queer and other people who are sexual and gender minorities (denoted by the umbrella term LGBTQ+) experience more physical and mental health problems than cisgender or heterosexual people, in part due to excess stress of experiencing stigma. Although it is important to document negative events in LGBTQ+ people's lives, it is also necessary to identify conditions that provide LGBTQ+ people with the opportunity to thrive. One key psychological facto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 243 publications
0
1
0
Order By: Relevance
“…31 Empirical support for the positive predictors of LGBTQ + workplace belonging and well-being remains limited. [32][33][34] The impact of workplace diversity trainings, allyship workshops, and employee and ally networks on workplace norms and employee attitudes, knowledge, skills, and confidence in speaking in support of sexuality and gender diversity and inclusion efforts has been explored in a number of studies, some of which have demonstrated success. [34][35][36] Though such efforts have also shown promise in fostering positive workplace experiences for LGBTQ + employees, few studies have empirically assessed their impact on LGBTQ + workplace belonging and well-being.…”
mentioning
confidence: 99%
“…31 Empirical support for the positive predictors of LGBTQ + workplace belonging and well-being remains limited. [32][33][34] The impact of workplace diversity trainings, allyship workshops, and employee and ally networks on workplace norms and employee attitudes, knowledge, skills, and confidence in speaking in support of sexuality and gender diversity and inclusion efforts has been explored in a number of studies, some of which have demonstrated success. [34][35][36] Though such efforts have also shown promise in fostering positive workplace experiences for LGBTQ + employees, few studies have empirically assessed their impact on LGBTQ + workplace belonging and well-being.…”
mentioning
confidence: 99%